2006
DOI: 10.1117/12.644554
|View full text |Cite
|
Sign up to set email alerts
|

200 Terawatt femtosecond laser based on optical parametric amplification in DKDP crystal

Abstract: 200 TW (pulse duration 45 fs at energy 9 J) peak power has been achieved experimentally using a Cr:forsterite master oscillator at 1250 nm, a stretcher, three optical parametrical amplifiers based on KD*P (DKDP) crystals providing 14.5 J energy in the chirped pulse at 910 nm central wavelength, and a vacuum compressor. The final parametrical amplifier and the compressor are described in detail. Scaling of such architecture to multipetawatt power is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…In Ref. [10], the dependence of the refractive index of this crystal on the wave frequency (the Sellmeier formula) was determined for an arbitrary degree of deuteration and it was found that, when pumped by the second harmonic of a neodymium laser at the central wavelength of an amplified pulse of 910 nm, ultra-wideband phase matching exists. Further studies [30,[52][53][54][55][56] confirmed these results and showed the prospectivity of using a DKDP crystal for broadband OPCPA.…”
Section: The Intermediate Opcpamentioning
confidence: 99%
See 4 more Smart Citations
“…In Ref. [10], the dependence of the refractive index of this crystal on the wave frequency (the Sellmeier formula) was determined for an arbitrary degree of deuteration and it was found that, when pumped by the second harmonic of a neodymium laser at the central wavelength of an amplified pulse of 910 nm, ultra-wideband phase matching exists. Further studies [30,[52][53][54][55][56] confirmed these results and showed the prospectivity of using a DKDP crystal for broadband OPCPA.…”
Section: The Intermediate Opcpamentioning
confidence: 99%
“…Our long-term experience of working with OPCPA [10,[13][14][15] showed that the efficiency of a parametric amplifier (the amplified pulse energy normalized to the pump pulse energy) in the experiment turns out to be 15%-25% lower than the theoretical one. This may be due to pump beam inhomogeneity, synchronization or alignment inaccuracy, poor antireflection, etc.…”
Section: The Intermediate Opcpamentioning
confidence: 99%
See 3 more Smart Citations